Women in law : a bio-bibliographical sourcebook - Salokar, Rebecca Mae, 1956-; Volcansek, Mary L., 1948- (Greenwood Press, 1996)
Includes profiles women who have made major contributions to the law through their work in the legal profession, scholarly legal research, and political activism directed at socio-legal reforms.